(untitled) (Global Journal of Management and Business Research, 2022)
Social Media taking the center-stage has augmented over the last decade in the arena of Business Development in an exponential progression It has been observed to be a pioneering force in determining the success as well as buoyancy of businesses in the long-run A theoretical exploration of the relevance of social media working as a catalyst- promoting innovation in the Indian Start-up Ecosystem shows that it has facilitated the progression of not just countless budding entrepreneurial ventures by providing an audience to entrepreneurs pitching novel ideas but also the economy as a whole articulated by it hitting the right notes in people who have a stake in the country s future This paper serves to compile relevant literature and provide a theoretical scrutiny of how social media has leveraged the Indian Start-up Ecosystem along with elucidating on how it has complemented policies directed towards improving the Start-up Economy in the country